Universities, inclusive development and social innovation: an international perspective - Brundenius, Claes; Göransson, Bo; Mello, Jose Manoel Carvalho de (Springer, 2017)
This book examines the ways in which universities can play a crucial role in inclusive development, social innovation and social entrepreneurship. It aims to prove the importance of inclusive development and inclusive innovation on economic growth and demonstrate the ways in which universities can be pioneers in this area through initiatives in social responsibility and social innovation. For example, providing access to a university education without discrimination of race, gender, income status, or other factors would help to diminish the increasing income differentials currently being experienced in many countries, especially in the developing world. The research and studies included in this book provide insight into possible actions that can be taken by universities and public and private shareholders in inclusive development, social innovation, social entrepreneurship and overall regional economic and social development.
Keywords: Développement inclusif; Développement social; Entrepreneuriat social; Innovation inclusive; Innovation sociale; Inégalités; Réservé UdeM; Rôle des universités; Université